Critical research gaps in understanding Southeast Asian women’s wildlife trade and use practices - Davis, Elizabeth Oneita (Frontiers in Conservation Science, 2022)
The hunting and consumption of wildlife is a global practice with practices that are socially nested, mediated, and shared across social categories, including gender. Research into wildlife trade increasingly recognizes the importance of understanding and investigating social drivers and processes of hunting and consumption. However, studies of social norms, motivations, and actions specific to women are still lacking within wildlife trade literature, particularly within Southeast Asia. Women are central to how a society operates and to societal practices, and they are fundamental actors in initiating change in these practices. In Southeast Asia, women are especially powerful actors within resident matrilineal and bilateral societies. This article will reflect on wildlife trafficking through the roles and activities of women. While women’s narratives are lacking across all current wildlife trade research, I will highlight in this article critical research gaps, gender-specific issues in methodology, and important research opportunities.